IMPLEMENTASI KEBIJAKAN PREMI ASURANSI NELAYAN DI KELURAHAN SAPOLOHE KECAMATAN KABUPATEN BULUKUMBA - Iman, Nurul Ihwanul; Mahsyar, Abdul; Parawu, Hafiz Elfiansyah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
The results of this study showed that the implementation of the policy regarding Fisherman Insurance Premiums. In the information indicator it could be concluded that  it had been  established well, seen from the coordination of the Bulukumba Fisheries Service with the Directorate of Licensing and Fishermen regarding the objectives and mechanisms of the BPAN program which was followed by the socialization carried out by the party itself to the fishing community in Sapolohe Village. In the policy content indicators, it could be concluded that the implementation of the Fisherman Insurance Premium Assistance Program policy had been carried out well, judging from the success rate of the implementation of the assistance being on target and in accordance with the disbursement provisions and the causes of events by the beneficiaries. On the indicator of community support, it could  be concluded that from this policy the community was very supportive and fully participates in accepting the policy regarding the existence of Fisherman Insurance Premium Assistance. In the potential distribution indicator, it could be concluded that in implementing the BPAN program the Head of the Bulukumba Fisheries Service had divided the tasks in each of his subordinate teams so that the implementation of the BPAN program run well and as expected.